A systematic literature review on quality of life in adult patients with psoriasis - Rahman, Saima; udddin, Nisar; Aman, Shahbaz; Sultan, Nadia; Butt, Ghazala; Rahman, Anila; Ahmad, Aafaque (Journal of Pakistan Association of Dermatologists, 2020)
Background Systematic literature reviews play a significant role in health-related decision making providing valuable information to the research community on effectiveness, the patient reported outcomes, and the cost of treatment if conducted properly. In this study, we conducted a systematic review with the aim to summaries research reported on psoriasis patient’s quality of life and investigating the social and psychological impairment of patients with psoriasis. Methods A systematic literature search on the electronic databases (PubMed, EMBASE, and Web of Science) was conducted to identify research carried on quality of life impairment in patients with psoriasis during the period 1st January 2007 till 30th September 2017. Selection criteria were defined, and studies were included accordingly. All the editorials, letters to the editor, and commentaries were excluded from the study. Results 128 articles were found that met the inclusion criteria and only 30 articles were included in this systematic literature review. Studies showed that psoriatic patients reported low self-esteem, pain/discomfort, and limited daily and social activities along with impaired sexual life. Conclusion Quality of life is significantly impaired by psoriasis and disease severity was associated with lower quality of life. Different dimensions including sexual functioning, work productivity, economic burden, and psychosocial activities are broadly addressed in the research and have been found to be significantly impaired by psoriasis.